Efecto de una intervención educativa nutricional en los hábitos alimentarios y estado nutricional de adolescentes del nivel secundario de la I.E San Pablo de la Luz-San Juan Bautista, 2023 - Cacique Tananta, Jessica Mariela (2024)
The objective of this research was to determine the effect of a nutritional educational intervention on the eating habits and nutritional status of secondary school adolescents at the I.E San Pablo de la Luz - San Juan Bautista. The study adopted a quantitative, quasi-experimental approach, with design of two groups (experimental and control), pre - test and post - test, and a longitudinal section. The sample was random probabilistic, with 134 adolescents. An attendance control, knowledge evaluation, eating habits questionnaire, IMC/E, T/E measurements and hemoglobin dosing were used to evaluate the results. The Chi Square statistical test validated the proposed hypothesis. The results showed an increase in hemoglobin levels from 41% to 59% after the intervention, indicating a positive impact of 18%. Regarding IMC/E, low weight remained at 0% in both evaluations, the normal range increased from 955% to 98%, showing an improvement of 25%, while overweight decreased from 3% to 0% and Obesity remained at 2%. For measure T/E, the results were stable: 15% of adolescents were short and 985% were normal, without significant changes between evaluations. In terms of eating habits, a significant improvement was observed: the prevalence of bad habits was reduced from 97% to 7%, regular habits increased from 3% to 18% and good habits increased from 0% at 75%At the knowledge level, 15% reached an excellent level, 66% presented a good level, 9% it showed a regular level and 10% maintained a bad level. These results confirm a statistically significant relationship between the educational intervention and the variables of nutritional status and eating habits (p < 0005), which led to the rejection of the null hypothesis and the acceptance of the alternative hypothesis. In conclusion, there is a significant statistical relationship between educational intervention, nutritional status and eating habits of high school adolescents at the I.E San Pablo de la Luz - San Juan Bautista in 2023.